Functional capacity, pulmonary and respiratory muscle strength in individuals undergoing hemodialysis - Simone Regina Posser; Sheila Cristina Cecagno-Zanini; Fabiana Piovesan; Camila Pereira Leguisamo
Abstract Introduction: Individuals with chronic kidney disease (CKD) undergoing hemodialysis (HD) present low cardiorespiratory fitness and functional capacity. Metabolic changes, due to the disease, can result in a variety of pathophysiological conditions that favor the development of respiratory muscle weakness. However, very little is known about the performance of the respiratory muscles and the influence of HD on them. Aim: To evaluate and correlate pulmonary function, functional capacity and respiratory muscle strength in patients with CKD undergoing HD. Methods: Cross-sectional study comprising 23 patients with CKD, that met the following inclusion criteria: patients of both genders, who perform HD three times a week for a minimum period of three months. Respiratory muscle strength was evaluated using a respiratory pressure meter, lung function through spirometry and functional capacity through the 6-minute walk test (6MWT) before the HD session. Results: All patients were male and mean age was 50.2 ± 15.8 years. The median duration of HD was 3 (1.5 to 6.0) years. The mean values obtained in comparison to those predicted were MIP% 36.0 ± 13.6, MEP% 49.5 ± 15.8, FVC% 93.8 ± 21.1, FEV1% 93.7 ± 21.1, FVC/VEF1% 104.1 ± 10.3, and 6MWT% 66.33 ± 20.53. A statistically significant positive correlation was observed between the 6MWT and MIP (r = .63, p =.001) and MEP (r = .67, p < .001), between the MIP and MEP (r =.79, p < .001) and between the FEV1 and FVC (r = .91, p < .001). Conclusion: Patients with CKD undergoing HD present changes in respiratory muscle strength, with the predicted values decreasing for age and gender, as well as the distance covered in the 6MWT, although, with normal spirometric values. Functional capacity was dependent on respiratory muscle strength, as well as the values of MIP and MEP, and the values of FVC and FEV1.